Care and protection for healthcare workers during a pandemic COVID-19: A descriptive qualitative study in Indonesia - Mochamat Helmi; Djayanti Sari; Andreasta Meliala; Laksono Trisnantoro (International Journal of Public Health Science (IJPHS), 2022)
This study aimed to explore the perspectives of care and protection of healthcare workers during the pandemic COVID-19 using a descriptive qualitative study in Indonesia. This study used a qualitative descriptive approach in COVID-19 National Referral Hospitals. The sample in this study is a medical team who actively engaged in delivering COVID-19 services. Purposive sampling was used to collect the sample. There were 45 respondents, with 22 men and 23 women taking part in this study. The qualitative data were analyzed using the content analysis. Three themes that emerge from the data analysis: health protection, legal protection, and incentive schemes. Health protection including calculation of the medical team's workload and lack of a systematic procedure for medical team quarantine. There was a lack of legal basis for medical practice in long-term disaster services. Dimension of incentive scheme, including incentives shift from rewards to demands, changes in incentive regulations, and discrepancy in incentive calculation. The medical team that provides services in a biological crisis, particularly for volunteers, must have a clear direction to follow legal protection and obvious health protection. By stressing protection and rewards for each level of the medical profession, it is hoped to boost motivation in actively participating and supporting the service of COVID-19 patients in critical conditions across Indonesia.